Endophytes of native grasses from South America: biodiversity and ecology - Iannone, Leopoldo Javier; Novas, María Victoria; Young, Carolyn A.; De Battista, Jose Pedro; Schardl, Christopher L. (Elsevier, 2019)
We review and present preliminary results of studies on cool-season grass endophytes native to South America. These fungi have been studied only in Argentina, where they have been detected in 36 native grass species. The hybrid Neotyphodium tembladerae is present in an extremely wide host range found in diverse environmental conditions, but some other endophytes seem to be strictly associated with one host species in a particular environment. In host species that inhabit different environments, the incidence of endophytes is highly variable among populations and in most of the cases is clearly associated with environmental conditions. In these native grasses, Neotyphodium presents a mutualistic behaviour, conferring enhanced growth, promoting the symbiosis with arbuscular mycorrhizal fungi, and inhibiting growth of pathogenic fungi. In native forage grasses, preliminary analyses indicate that some Argentinian endophytes can produce lolines but are unlikely to produce lolitrem B or ergot alkaloids.